Methodology to evaluate interface of educational computer game - Omar, H. M. (IEEE, 2011)
Game is an application that is popularly used in teaching and learning by some of educational institution to-date. Educational computer game (ECG) is a game being used for teaching and learning. Comprehensive methodology that consist of techniques and tools need to be developed to assist the development of ECG. ECG is an application that combines elements of fun and education and the evaluation criteria need to be able to covers all the important criteria. There are 5 heuristics identified; interface, pedagogical, content, playability and multimedia. Two techniques are identified to be used in evaluation process; PHEG for expert evaluators and PAEG for real user. The tool, online evaluation system (AHP-HeGES) is the tool that can be used to simplify the evaluation process. This research is important because it can help the game developers and educationist to conform the important elements that need to be exists in any ECG through evaluation process.